Challenges of diversity and inclusion and the need for change . (16th June 2022) - Oliveros, Estefania; McHugh, Stephen; Brito, Daniel; Yancy, Clyde
Graphical Abstract: Graphical Abstract Challenges of diversity and inclusion in the Cardiovascular Work Force. We demonstrate the race and ethnicity distribution in the US population, Medical Schools, Active Physician and Cardiologist.